2015
DOI: 10.1109/te.2014.2358575
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Gaps in Circuits Textbooks: A Comparative Study

Abstract: Many university-level electrical engineering courses continue to use textbooks as curriculum scaffolds, prescribed texts, and/or reference volumes. Textbook reliance is even more pronounced in courses that teach foundational principles of the discipline, such as introductory circuit theory. This paper reports on the conceptual coverage of introductory electric circuit theory as presented in textbooks. More specifically, a comparative study of six texts was performed using an analytic framework based on prior r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…A generalised concept of field is usually not taught in depth in lower secondary school science, but would make students able to map the gravitational field in a source domain to the corresponding electric field in the target domain and this way get a grasp of the concept of potential. It appears from our results that potential is a conceptual gap as described by Sangam and Jesiek (2015), and that some students would probably be able to map the analogies involving height and height difference if they had this concept as a tool. In line with Stocklmayer (2010), we suggest that further research should be undertaken in order to elicit whether and in what ways the concepts of field and potential should be introduced for supporting young students understanding of electric circuits and improving their understanding of electric voltage as a key concept.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A generalised concept of field is usually not taught in depth in lower secondary school science, but would make students able to map the gravitational field in a source domain to the corresponding electric field in the target domain and this way get a grasp of the concept of potential. It appears from our results that potential is a conceptual gap as described by Sangam and Jesiek (2015), and that some students would probably be able to map the analogies involving height and height difference if they had this concept as a tool. In line with Stocklmayer (2010), we suggest that further research should be undertaken in order to elicit whether and in what ways the concepts of field and potential should be introduced for supporting young students understanding of electric circuits and improving their understanding of electric voltage as a key concept.…”
Section: Discussionmentioning
confidence: 74%
“…When students consider voltage, they often see it as a consequence rather than a cause of electric current (Cohen, Eylon, & Ganiel, 1983), have problems differentiating between voltage and current, or they do not see why both concepts are needed (Koponen & Huttunen, 2013). It is shown that even university students in physics have difficulties understanding relations between concepts (Kokkonen & Mäntylä, 2017), and that textbooks in electrical engineering at university level tend to contain 'conceptual gaps' where important conceptual features are missing in the treatment of electric circuits (Sangam & Jesiek, 2015).…”
Section: Student Conceptions About Electric Circuitsmentioning
confidence: 99%
“…Given this introduction about the importance of circuit analysis course, many researches have been devoted to the success of the students in this course [5]. These approaches include, but not limited to, improving teaching style [6,7], text book selection [8], and improving teaching materials [9]. Despite of these researches, further steps need to be taken to fulfill the gaps in the content of this important course.…”
Section: Introductionmentioning
confidence: 99%
“…The reading and reflection sections will contain content related to key misconceptions often demonstrated by struggling students and are meant to supplement typical textbooks which either have conceptual gaps or present incomplete or misleading models and analogies. A recent review by Sangam and Jesiek presents a comparative study of conceptual gaps in popular circuits textbooks [11]. As will be discussed in the Beta-Testing Section, the importance of providing targeted and concise readings for struggling students will be critical to the efficacy of the system for students lacking commitment to invest significant time to study the material.…”
Section: Reading and Reflection Exercisesmentioning
confidence: 99%
“…A second key reason which is hypothesized as to why students struggle in gateway courses in general and in electric circuits in particular is a student's use of faulty mental models. For example, common student misconceptions exhibited in basic circuit analysis tasks include belief that a battery is a source of a constant current, belief that current is consumed and belief that charge flow is a sequential process [6]- [11]. While some of these misconceptions may be readily be corrected, others are more robust [12] requiring considerable intervention to rectify.…”
Section: Introductionmentioning
confidence: 99%